THE ROLE OF KOMUNITAS GURU BELAJAR (KGB) IN CREATING INDEPENDENT TEACHERS OF ISLAMIC EDUCATION - Syukron Ma'mun (Postgraduate Program, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The objectives of this study were to reveal 1) the efforts of the Komunitas Guru Belajar (KGB) in realizing Islamic religious education teachers who are self regulation learning; the role of the Komunitas Guru Belajar (KGB) in realizing Islamic religious education teachers who are self regulation learning; and the supporting factors and inhibiting factors from Komunitas Guru Belajar (KGB) in realizing Islamic religious education teachers who are self regulation learning. The approach used is a qualitative approach. This type of research used field research. The data sources used are primary and secondary data sources, Primary data sources are the founder of the KGB, the head of the KGB, Islamic religious education teachers, and guidebooks. Secondary data sources are books as references, magazines, internet, and articles related to this research. The data analysis technique uses the Milles and Huberman model, namely data analysis using data reduction techniques, data display and data conclusions in the field. The results showed that, the efforts of the Komunitas Guru Belajar (KGB) in realizing Islamic religious education teachers who are self regulation learning in Pekalongan namely through its activity programs, where KGB Pekalongan has several programs that are quite varied and flexible. The role of the Komunitas Guru Belajar (KGB) in realizing Islamic religious education teachers who are self regulation learning in Pekalongan is as a forum for teachers as well as supporting teachers to develop their teaching competences, Besides that, it also provides opportunities for Islamic religious education teachers to collaborate with fellow teachers and other communities to produce work or achieve common goals, have the opportunity to identify, choose, plan, and develop careers according to their potential aspirations. The supporting factors for the KGB in realizing Islamic religious education teachers who are self regulation learning in Pekalongan are: independent learning policy by the Indonesian minister of education and culture, support from local governments and official services, collaboration across communities and relevant organizations, and good human resources.